Low‐Permeability Poly(ether Ether Ketone)‐Based Ampholytic Membranes. Issue 6 (17th May 2016) - Narducci, Riccardo; Pasquini, Luca; Chailan, Jean‐François; Knauth, Philippe; Di Vona, Maria Luisa
Abstract: Ion‐exchange membranes based on sulfonated and sulfaminated poly(ether ether ketone) were prepared by a modified sulfamination route. In a first step, poly(ether ether ketone) was sulfonated. The sulfonic acid groups were then transformed into chlorosulfonic moieties by reaction with thionyl chloride. A proportion of the chlorosulfonic functionalities reacted with dimethylamine to give basic sulfonamide groups, whereas those remaining were hydrolyzed back to sulfonate moieties obtaining, after immersion in acidic solution, an ampholytic polymer. The thermal, mechanical, electrical, and permeability properties of these amphoteric membranes were characterized. These membranes exhibit good thermal and mechanical stability and ultra‐low vanadium ion permeability. The type and value of ion conductivity can be adjusted by the choice of acidic or basic medium. The tunable ion conductivity and the low ion permeability are suitable characteristics for the development of high‐performance separator membranes. Abstract : Good conduct : A simple and inexpensive synthesis leading to ampholytic membranes with ultra‐low cation permeability is reported (see figure). Such membranes can be important for water purification and electrochemical energy technologies, such as redox flow batteries.